Molybdenum carbide nanoparticles assembling in diverse heteroatoms doped carbon matrix as efficient hydrogen evolution electrocatalysts in acidic and alkaline medium. (January 2021) - Wu, Shifan; Chen, Mengying; Wang, Weiwen; Zhou, Jiabei; Tang, Xinru; Zhou, Dali; Liu, Can
Abstract: Developing economical and efficient electrocatalysts toward hydrogen evolution reaction (HER) plays a crucial role in promoting the utilization of hydrogen energy. Herein, a bottom-up strategy is exploited to synthesize ultrafine molybdenum carbide (Mo2 C) nanocrystals assembling in boron, nitrogen co-doped carbon matrix (BNC). The BNC framework not only increases the dispersibility of carbide particles, but also provides additional active sites to intensify HER performance. Moreover, in comparison with mono-heteroatom modification, the catalyst decorating with B and N simultaneously is demonstrated to be a generalist which can efficaciously catalyze HER in both acidic and alkaline electrolyte. In-depth studies show that N-doping is conductive to capturing protons in acid while B-doping facilitates the adsorption and dissociation of water in alkali. This work may shed some light on the rational design and manufacture of HER electrocatalysts with high compatibility to distinct electrolytic environments. Graphical abstract: Mo2 C@BCN as an efficient electrocatalyst for hydrogen evolution. Image 1